Seismic Retrofit of RC Building with Elastic Stage of Buckling-Restrain Braces - Thipprapan, Thanawat; Jarasjarungkiat, Amphon; Saingam, Panumas; Petchsasithon, Arthit (My University, 2023)
Seismic retrofit of a reinforced concrete (RC) building using a buckling-restrained brace is an innovative method to improve the seismic performance of the existing RC buildings to resist damage from the future earthquake. This research proposes a simple method to retrofit RC buildings with buckling-restrained braces (BRBs). A 4-story school reinforced concrete building in Thailand is selected as a target building. The analysis results of the existing RC building indicate that the structure cannot withstand the seismic force under the newest code, which was published in 2021. There were failures at the columns of the 1st–3rd floors, in which lateral displacements exceeded the current seismic design standard. After retrofitting the target building by the proposed method with BRBs, it was found that the lateral displacements are reduced and the target RC building can withstand the seismic demand of the newest code. Therefore, the retrofitted building can be resisted future earthquakes. This shows the effectiveness of the introduced retrofit method.
Keywords: Buckling-restrained braces; Elastic stage; RC buildings; Retrofitting